International perspectives on participation - Ortega, Jaime, 1970- (Advances in the economic analysis of participatory and labor-managed firms ;, 2014)
This volume analyses employee participation in under-researched countries and whose economic institutions differ from the Anglo-American context. The first three papers are dedicated to China. In a context in which economic decisions made by companies are closely influenced by the political institutions and practices, the extent to which Chief Executive Officers (CEOs) have the ability to make autonomous decisions is not to be taken for granted. The volume explores whether the executive labor market and firms' executive compensation practices differ from the Western context. Evidence on the role of trade unions in Chinese companies is also analyzed. The rest of the volume includes empirical evidence from Europe, Japan, and Korea, and focuses on high-involvement work practices. The main questions that the volume addresses are the incidence and determinants of these practices and their effects on firm performance. Evidence on the incidence contributes to understanding the importance of these practices in an international context, and the analyses on the determinants and effects help understand how the main trade-offs play out in different institutional contexts.